Pembuktian Penyelesaian Sengketa Sertifikat Tanah Pada Pengadilan Tata Usaha Negara Medan - Suri, Dwi Atika; Ramadhani, Rahmat (Universitas Muhammadiyah Sumatera Utara, 2024)
Land is one of the most important aspects of human life. Soil has broad functions for humans. Starting from human life originating from the soil, growing and developing and carrying out activities on the soil to humans being buried in the soil in order to fulfill their promise to the creator. The benefits of land for humans are so great that human life cannot be separated from the role and function of land rights. The research method used is normative juridical research, namely legal research carried out by examining library materials or secondary data. Basically, all types of agrarian conflicts arise as a result of gaps related to agrarian resources, especially gaps in land control, allocation, perceptions and conceptions, as well as conflicting or overlapping laws and policies. One of the most important things that a judge must do in examining state administrative disputes is proof. In state administrative courts, the model of proof is formal truth referring to the object of the dispute, namely the official's decision which is detrimental to the parties, and paying attention to material truth, namely photographing and paying attention to the process of occurrence, or the emergence of the object of the state administrative lawsuit.